2009
DOI: 10.1159/000226428
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Psychosocial Factors and Onset of Multiple Sclerosis

Abstract: Objective: The aim of this study was to investigate the influence of psychosocial variables on patients with multiple sclerosis (MS) and the relationship between these variables and the onset of MS. Background: The current evidence indicates that many types of psychosocial factors are involved in the development and relapse of MS, and it has been suggested that they could serve as predictors as well. So far, little has been reported on the effect of psychosocial factors on MS and the relationship between psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 26 publications
3
45
0
4
Order By: Relevance
“…Only 1 of the 6 studies concerning onset was designated as a retrospective cohort study [30] . The remaining 5 [23,39,[44][45][46] were case-control studies, and 1 of them, by Warren et al [46] , elaborated on the results of a previous publication and was excluded. Regarding MS relapse, 9 studies were designated as cohort studies (follow-up) [26][27][28][29][32][33][34][35][36] , 3 as case-control studies [37,40,43] , 5 as cross-sectional studies, and 1 as a case series.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only 1 of the 6 studies concerning onset was designated as a retrospective cohort study [30] . The remaining 5 [23,39,[44][45][46] were case-control studies, and 1 of them, by Warren et al [46] , elaborated on the results of a previous publication and was excluded. Regarding MS relapse, 9 studies were designated as cohort studies (follow-up) [26][27][28][29][32][33][34][35][36] , 3 as case-control studies [37,40,43] , 5 as cross-sectional studies, and 1 as a case series.…”
Section: Resultsmentioning
confidence: 99%
“…As seen in table 2 , there is limited information about disease duration and disability, with a trend towards below 10 years and limited disability, respectively. Two case-control studies [39,44] focused on stress occurrence 1 year prior to onset of symptoms, one study at 2 years prior to onset [45] , and one study at 3 years prior to diagnosis of MS [23] .…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results already achieved show significant effects on day-to-day consequences in patients with adjustment to illness. Previous research has shown that it is connected to actions of family and social reciprocity, has a positive effect on the overall health of patients 16 and on the life of caregivers 17,18 , reducing its burden [19][20][21] . High levels of social support are also associated with high levels of HRQoL and low levels of depression among patients with MS 4,6,8,22 .…”
mentioning
confidence: 99%
“…Urinary incontinence affects the social, psychological, occupational, familial and physical aspects of the patients' lives and limits their ability to enjoy daily activities, social relations, traveling and personal relationships and imposes heavy costs on the patients and the healthcare systems (8,9). Psychological manifestations of MS include anxiety, stress, depression, cognitive disorders, irritability and anger, with the most prevalent ones being anxiety, stress and depression (10). About 48% of patients experience anxiety, stress and depression in the first year of diagnosis with MS, and these symptoms tend to highly affect the patients' quality of life (11).…”
Section: Introductionmentioning
confidence: 99%